KECENDERUNGAN REKLAMASI WILAYAH PANTAI DENGAN PENDEKATAN MODEL DINAMIK - Lestario Widodo (Jurnal Teknologi Lingkungan, 2005)
Big cities, especially those with have coastal area, in their development processwill face the problem of limiting area, either for human setlemen or other purposes. One effort to solve the problem is by doing a coastal reclamation which still has problems until now due to the negative impacts resulted. A dynamic model had been developed to exemine the causality of a reclamation phenomenon. Which a simple dynamic model it is known already that investor interest in coastal reclamation is defined by result potential in future, which is reflected by a beneficial land conversion price and relatively small delay period.